The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/nl400343a
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Composite Enabled Nanotextured Si Photoanode for Efficient Solar Driven Water Oxidation

Abstract: We present a study of a transition metal oxide composite modified n-Si photoanode for efficient and stable water oxidation. This sputter-coated composite functions as a protective coating to prevent Si from photodecomposition, a Schottky heterojunction, a hole conducting layer for efficient charge separation and transportation, and an electrocatalyst to reduce the reaction overpotential. The formation of mixed-valence oxides composed of Ni and Ru effectively modifies the optical, electrical, and catalytic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 59 publications
(73 reference statements)
3
87
0
5
Order By: Relevance
“…0.1 %a t6 40 nm (Figure 7a), accompanied by a5 0% increase of OER photocurrent at 12.3 Vv ersus RHE in an eutral electrolyte (pH 7.2) under AM1.5G (Figure 7b). [23] Forw ater reduction, photolithographically prepared Si micropillars also showed enhanced HER photocurrent density from 8to9mA cm À2 at 0Vversus RHE (1m HClO 4 ,A M1.5G with l > 635 nm) compared to planar p-Si(100) electrodes. [12] Similarly,both InP nanopillars (Figure 7c) [20] and InP nanowire arrays (Figure 7d) [5] were demonstrated to suppress the reflectance of polished planar InP from ca.…”
Section: Surface Texturizationmentioning
confidence: 94%
See 2 more Smart Citations
“…0.1 %a t6 40 nm (Figure 7a), accompanied by a5 0% increase of OER photocurrent at 12.3 Vv ersus RHE in an eutral electrolyte (pH 7.2) under AM1.5G (Figure 7b). [23] Forw ater reduction, photolithographically prepared Si micropillars also showed enhanced HER photocurrent density from 8to9mA cm À2 at 0Vversus RHE (1m HClO 4 ,A M1.5G with l > 635 nm) compared to planar p-Si(100) electrodes. [12] Similarly,both InP nanopillars (Figure 7c) [20] and InP nanowire arrays (Figure 7d) [5] were demonstrated to suppress the reflectance of polished planar InP from ca.…”
Section: Surface Texturizationmentioning
confidence: 94%
“…[23] Upon the incorporation of RuO x ,the Ni II /Ni III ratio changed from 0.86 to 0.35 as revealed by XPS,indicating that the NiRuO x film was Ni III -rich. By depositing this NiRuO x film on FTO, the dark OER overpotentials at 10 mA cm À2 decreased from 1829 (bare FTO) to 797 mV versus RHE (pH 7.2), which outperformed the pure NiO x film that needed a1 043 mV overpotential to drive the same current density.F or the n-Si/NiRuO x photoanode under AM1.5G illumination, an onset potential of 1.08 Vv ersus RHE (pH 7.2) was observed, with ap hotocurrent density of 0.94 mA cm À2 at 1.23 Vv ersus RHE.…”
Section: Noble Metals As Oer Cocatalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies confirmed long-term stable water splitting on nanostructured InGaN/GaN photoanodes in 1 M NaOH electrolyte with photocurrent densities in the sub-mA/cm 2 range under AM1.5G one sun illumination. 26,51 By developing an effective protection strategy to prevent the oxidation of the underlying Si substrates, 52 InGaN nanowire photoanodes integrated on Si have the potential to enable high efficiency and highly stable solar water splitting. Moreover, heterostructures based on such superior quality InGaN nanowires also hold tremendous promise for realizing deep visible and near-infrared light emitting diodes and lasers on a Si platform for full color displays and on-chip optical communications.…”
Section: -mentioning
confidence: 99%
“…Mn [62], Fe [63], Ni [26,[64][65][66][67][68][69][70] and Ir [71], have been used to protect n-Si photoanodes for water oxidation in strongly alkaline or acidic electrolytes [72]. Protection of III-V and II-VI semiconductors in aqueous photoelectrochemical systems has also been studied.…”
Section: Introductionmentioning
confidence: 99%